Cost-Effectiveness of Dipeptidylpeptidase-4 Inhibitors Added to Metformin in Patients With Type 2 Diabetes in China - Lin, Wen-Qiang; Cai, Zhong-jie; Chen, Tingting; Liu, Mao-Bai; Li, Na; Zheng, Bin (Frontiers in Endocrinology, 2021)
Purpose: Dipeptidylpeptidase-4 (DPP-4) inhibitors, including linagliptin, alogliptin, saxagliptin, sitagliptin and vildagliptin, are used for the treatment of type 2 diabetes mellitus (T2DM) patients in China. This study assessed the economic outcomes of different DPP-4 inhibitors in patients with T2DM inadequately controlled with metformin in the Chinese context. Materials and methods: In this study, the validated Chinese Outcomes Model for T2DM (COMT) was conducted to project economic outcomes from the perspective of Chinese healthcare service providers. Efficacy and safety, medical expenditure, and utility data were derived from the literature, which were assigned to model variables. The primary outputs of the model included the lifetime costs, quality-adjusted life years (QALYs) and incremental cost-effectiveness ratio (ICER). One-way and probability sensitivity analysis was conducted to assess the potential uncertainties of parameters. Results: Of the five competing strategies, alogliptin 25 mg strategy yielded the most significant health outcome, which associated with improvements in discounted QALY of 0.007, 0.014, 0.011 and 0.022QALYs versus linagliptin 5 mg, saxagliptin 5 mg, sitagliptin 100 mg and vildagliptin50 mg, respectively. The sitagliptin 100 mg strategy was the cheapest option. The ICER of alogliptin 25 mg against sitagliptin 100 mg strategy was $6,952 per additional QALY gained, and the rest of strategies were dominated or extended dominated. The most influential parameters were the cost of DPP-4 inhibitors and their treatment efficacy. Conclusions: These results suggested that alogliptin was a preferred treatment option compared with other DPP-4 inhibitors for Chinese patients whose T2DM are inadequately controlled on metformin monotherapy.